(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
28 moss species grow on the territory of regional natural memorial “Derevostiy akatsii biloi”. Chiefly, these species are typical components of the Nothern Black Sea Coast regional bryoflora. Such non-vascular plants are typical for deciduous forests and different tree afforestations. 6 species – Porella platyphylla, Frullania dilatata, Radula complanata, Synrichia papillosa, Orthotrichum lyelii, O. patens – are “regionally rare" bryophytes of the Kherson region. Nyholmiella gymnostoma species included in the Red Data Book of European Bryophytes. Place the growth of bryophytic tied up with Acer negúndo, Celtis occidentalis, Gleditsia triacanthos, Quercus robur, Robinia pseudoacacia, Ulmus minor trees. Mosses grow on trunks and bristles, on rotten bark and rotten wood (stumps, broken trunks and fragments of branches), and on soil also. We found that epiphytic, epicidal and epigeoid briocomplexes had different structures and species diversity. Moss groups are combined mainly by 9–11 species on the wood bark (on Acer negúndo – 15 species), this index increases to 13–17 species on the epiphytic substrates, on soil grow only 4 species. There is a greater number of moss species and a larger area of moss berries on those trees where the bark is thicker and more cracks. The moss complex structures are similar on different trees. Small cushions groups of Orthotrichum pumilum, O. diaphanum, O. speciosum, O. affine are dominate in epiphytic groupings. Roles of flat-mat groups from Leskea polycarpa, Pylaisia polyantha, Hypnum cupressiforme, H. cupreforme var. filiforme are slightly less. Amblystegium serpens var. saxicola, Hypnum cupressiforme var. lacunosum and other mixed with them. The number of Orthotrichum species is becoming smaller. And the importance of pleurocarpos species such as Brachytheciastrum velutinum, Brachythecium salebrosum, Amblystegium serpens, Homalothecium sericeum are increase on tree-stumps, rotten wood, rotten bark. The epigeoid fraction includes some polysubstrate moss species with wide ecological amplitudes (Ceratodon purpureus, Leptodictyum riparium et all). Some steppe and shrubbery mosses migrated to the beds of deciduous trees and wreckage of rotten wood. Ceratodon purpureus, Ptychostomum moravicum, P. capillare, Syntrichia ruralis, S. ruraliformis, Grimmia pulvinata were detected here. In general, the bryophloristical composition and structure of the regional nature memorial “Derevostiy akatsii biloi” is an example of the changes that took place in the bryophlore of the Lower Dniper sands as a result of afforestation. The growth of role of epiphytic and epixyl mosses, primarily species of the Orthotrichaceae family, is enhanced due to the emergence of new substrates. The participation of the Pottiaceae mosses representatives is weakening in parallel. This family is dominant in the zonal steppe bryophlora of the Northern Black Sea Coast. Typical ground moss species disappear, with the exception of polysubstrators, which biology allows them to live on trees. Therefore the possibility of restoring natural psymunoid-steppe brioflora in previously planted areas, where the tree plant is destroyed, may be much slower.